Impact of Covid-19 on Education Across the World - Dr. Ravi Sidhu (International Journal of Engineering and Management Research, 2021)
The global epidemic of the Corona virus has wreaked havoc on a variety of industries. One of them is the education industry. Due to Covid-19, governments all around the world have begun temporarily closing schools and colleges. School and university closures would not only have a short-term impact on the continuity of learning for India's more than 285 million young learners, but will also have far-reaching economic and societal ramifications as the days pass with no rapid way to stop the breakout of Covid-19.